A new device to inseminate cows at the base of the uterine horns. (7th December 2016) - García‐Peña, O; Rangel‐Santos, R; Rodríguez‐De Lara, R; Apodaca‐Sarabia, CA; Maldonado‐Simán, E
Content: A new device (Chapingo device) to deposit semen at the base of the uterine horns of cattle was developed at Universidad Autonoma Chapingo, Mexico. Nine Holstein heifers were inseminated by transvaginal laparoscopy, using a laparoscope for cattle and the Chapingo device. A dose of sexed semen (2.1 × 10 6 spermatozoa) was deposited at the base of the uterine horn ipsilateral to the ovary where the preovulatory follicle was identified. Insemination was achieved in all the heifers, taking on average 13.7 ± 3.1 min per animal. In all cases, it was possible to see both ovaries, the base of the uterine horns and the oviducts. After the procedure, none of the heifers showed any type of complications such as haemorrhage, adhesions or trauma. On days 21 and 22 after insemination, four of the nine heifers (44.4%) returned into oestrus; on day 30 after insemination, one heifer was found to be pregnant by ultrasound. The results show the feasibility of generating pregnancies by transvaginal laparoscopy in heifers inseminated with sexed semen.